2014
DOI: 10.1007/s10120-014-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving trends in survival of patients who receive chemotherapy for metastatic or recurrent gastric cancer: 12 years of experience at a single institution

Abstract: Background The aim of this retrospective study was to evaluate the changes in clinical features and treatment outcomes of the patients with metastatic or recurrent gastric cancer (MRGC) treated in the past 12 years. Results There were 880 patients (23 %) in period 1, 1573 (40 %) in period 2 and 1435 (37 %) in period 3. The most commonly used first-line chemotherapy regimen was fluoropyrimidine with/without platinum (72 %) for all periods. The use of second-and third-line chemotherapy was slightly but significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
17
3
Order By: Relevance
“…ECOG PS, primary metastatic vs. recurrent disease, single vs. combination first-line chemotherapy). The median OS of 18 months in patients with surgical resection appears encouraging, considering previously reported median OS of RPMGC patients who received palliative chemotherapy 11,[26][27][28][29][30] . Nonetheless, randomized trials are necessary to prove whether this OS benefit was caused by the effect of palliative surgical resection itself or the patients' favorable baseline characteristics, although the beneficial effect of surgical resection was consistent even after PSM including age and PS.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…ECOG PS, primary metastatic vs. recurrent disease, single vs. combination first-line chemotherapy). The median OS of 18 months in patients with surgical resection appears encouraging, considering previously reported median OS of RPMGC patients who received palliative chemotherapy 11,[26][27][28][29][30] . Nonetheless, randomized trials are necessary to prove whether this OS benefit was caused by the effect of palliative surgical resection itself or the patients' favorable baseline characteristics, although the beneficial effect of surgical resection was consistent even after PSM including age and PS.…”
Section: Discussionmentioning
confidence: 71%
“…Although many studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17] have suggested the OS benefit of surgical resection such as palliative gastrectomy or metastasectomy, especially for liver metastasis, in RPMGC, the role of palliative resection is still controversial due to high probability of selection bias in most studies 3 and some reports showing lack of definite benefit of surgery [31][32][33] . Furthermore, the results of most previous retrospective studies [4][5][6][7][8][9][10][11][12][13] and meta-analysis [14][15][16][17] were derived from heterogeneous patient populations, including those who had not received chemotherapy as well as those who had undergone it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy was the standard of care for patients with relatively advanced gastric cancer and thanks to the introduction of new adjuvant chemotherapy regimens, overall survival (OS) among patients with gastric cancer has increased significantly during the past few years. [1][2][3] However, since gastric cancer was usually asymptomatic in early stages, researchers found it difficult to stratify and treat those patients. 4 The lack of a reliable standard to distinguish those really at high risk has made it hard for us to identify patients who would benefit from adjuvant chemotherapy when considering OS.…”
Section: Introductionmentioning
confidence: 99%
“…[911] Although these clinical trials have been demonstrated that second-line chemotherapy can significantly prolong the survival of patients with progressive or recurrent gastric cancer, compared to that of the patients with supportive care alone, [2,11] there is controversy over the benefit of third-line chemotherapy due to the lack of evidence. In this regard, little information concerning the survival advantage of third-line chemotherapy is available.…”
Section: Introductionmentioning
confidence: 99%